The Mechanical Property and Strengthening Mechanism of the Mg-0.5Zn-0.2Mn-0.2Sm-0.3La alloy. Issue 1 (June 2021) - Fu, L; Guo, C R; Lu, L; Jia, Z; Le, Q C
Abstract: Tensile properties at TR with different stretch velocity, and tensile properties at T150°C were investigated in this study, and the strengthening mechanism was discussed preliminarily. Firstly, tensile properties of the Mg-0.5Zn-0.2Mn-0.2Sm-0.3La alloy at TR with the stretch velocity increases from 1 to 6 mm·min −1, and results suggest that the studied alloy exhibits low strength sensitivity as both of Rm and Rp0.2 maintaining at 240 MPa and 190 MPa, which is attributed to the not enough time for the dynamic recrystallization at the higher deformation velocity. Meanwhile, as the stretch velocity increases, although A increases first and then decreases because of the more stress concentration near grain boundaries, A maintains above 20%, suggesting the good plastic sensitivity. Secondly, when stretched at T150°C both of Rm and Rp0.2 of the Mg-0.5Zn-0.2Mn-0.2Sm-0.3La alloy decrease compared to that at TR, which is attributed to the increased dislocation movement at the higher temperature, while A increases at T150°C than at TR because of the decreased critical shear stress at the higher temperature. Even though, because the Mg12 La phases impede the dislocation movement and the Sm atoms result in the solution strengthening, the mechanical properties of the Mg-0.5Zn-0.2Mn-0.2Sm-0.3La alloy are still higher than that of the Mg-0.5Zn-0.2Mn alloy at the higher temperature.